2019
DOI: 10.21203/rs.2.11882/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of pelvic organ prolapse in women, associated factors and impact on quality of life in rural Pakistan: population-based study.

Abstract: Background: Pelvic organ prolapse (POP) is a gynecological condition resulting from pelvic floor dysfunction in women. The objective of this study is to estimate “the prevalence of pelvic organ prolapse” associated factors, duration and impact on women's quality of life in rural Pakistan. Methods: A cross-sectional study was conducted with a three stage random sampling strategy.Three health centers were selected and selected Lady Health Workers from each health center interviewed a random sample of women in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
4
0
0
Order By: Relevance
“…This finding was supported by (Masenga et al, 2018) who illustrated a significant relation between the severity of prolapse and the educational level in the Tanzanian rural community. Moreover, our findings are in agreement with (Jokhio et al, 2020) who found the severity of POP was higher among illiterate Pakistan women as compared to educated women with a low rate of reporting and consultation among them.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding was supported by (Masenga et al, 2018) who illustrated a significant relation between the severity of prolapse and the educational level in the Tanzanian rural community. Moreover, our findings are in agreement with (Jokhio et al, 2020) who found the severity of POP was higher among illiterate Pakistan women as compared to educated women with a low rate of reporting and consultation among them.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were similar to the findings of (Laganà et al, 2018) that revealed POP symptoms were negatively impacting women QOL in all domains (physical function, role limitation, social activities, occupational activities, and sexual). Also, these findings were consistent with a study conducted in Pakistan by (Jokhio et al, 2020), and found oldaged women reported a great impact on their daily life activities which including; hygiene, home/work life, and social life versus the middle-aged women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The Quality of Life among women with POP at MRRH is poor with an overall mean score of 45.5%. This is similar to ndings from high income countries where women with POP had a poor QOL (34,35). Pelvic organ prolapse affects women's physical, social, emotional, sleep and sexual performance.…”
Section: Discussionsupporting
confidence: 83%